Pilot Efficacy of a DriveFocus™ Intervention on the Driving Performance of Young Drivers - Alvarez, Liliana; Classen, Sherrilene; Medhizadah, Shabnam; Knott, Melissa; He, Wenqing (Frontiers in Public Health, 2018)
Road traffic injuries are the leading cause of death for youth between the ages of 15 and 29 around the world. A need remains for evidence-based interventions that can improve the underlying skills of young drivers, including hazard perception and anticipation. This pilot study investigated the preliminary impact of a six session DriveFocus™ intervention on the ability of young novice drivers (mean age = 18.6, SD = 2.12) to detect (visual scanning), and respond (adjustment to stimuli) to critical roadway information. Using a CDS-200 DriveSafety™ simulator, drives were recorded and sent to a blinded evaluator (occupational therapist), who scored the recorded drives for number and type (visual scanning and adjustment to stimuli) of errors. We observed a statistically significant decline in the number of visual scanning [t(34) = 2.853, p = 0.007], adjustment to stimuli [t(34) = 3.481, p = 0.001], and total driving errors [t(34) = 3.481, p = 0.002], among baseline and post-test 2.